2011
DOI: 10.1093/ecam/nep173
|View full text |Cite
|
Sign up to set email alerts
|

The Traditional Japanese Medicine Rikkunshito Promotes Gastric Emptying via the Antagonistic Action of the 5‐HT3 Receptor Pathway in Rats

Abstract: The traditional Japanese medicine rikkunshito ameliorates the nitric oxide-associated delay in gastric emptying. Whether rikkunshito affects gastric motility associated with 5-hydroxytryptamine (serotonin: 5-HT) receptors or dopamine receptors is unknown. We examined the effects of rikkunshito on the delay in gastric emptying induced by 5-HT or dopamine using the phenol red method in male Wistar rats. 5-HT (0.01–1.0 mg kg−1, i.p.) dose dependently delayed gastric emptying, similar to the effect of the 5-HT3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 38 publications
1
74
0
1
Order By: Relevance
“…These findings might indicate the possibility that RKT clinically ameliorates POI through improvements in both Until now, several mechanisms for the gastroprokinetic action of RKT have been reported. RKT increases gastric emptying by the 5-HT 3 receptor antagonism in rats (2). Efficacy of RKT was reported to be comparable to the 5-HT 3 antagonist ondansetron.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These findings might indicate the possibility that RKT clinically ameliorates POI through improvements in both Until now, several mechanisms for the gastroprokinetic action of RKT have been reported. RKT increases gastric emptying by the 5-HT 3 receptor antagonism in rats (2). Efficacy of RKT was reported to be comparable to the 5-HT 3 antagonist ondansetron.…”
Section: Discussionmentioning
confidence: 95%
“…These flavonoids also induce prokinetic ability through improvement of ghrelin release owing to the 5-HT 2B and 5-HT 2C receptor antagonistic action (3). Moreover it was demonstrated that hesperidin showed pharmacological efficacy in enhancing gastric motility via antagonism of a 5-HT 3 receptor-associated pathway (2). These flavonoids and herbs may have multiple actions including anti-inflammatory ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, increasing evidence from experimental animal models has shown that rikkunshito ameliorates several types of anorexia (23,24,57). It has been reported that with rikkushito there is an increase in the secretion of the orexigenic hormone ghrelin by the inhibition of 5-HT2B/2C receptors, an enhancement of ghrelin receptor (GHSR) signaling efficiency, and a facilitation of gastric emptying and gastric adaptive relaxation, all of which may contribute to ameliorate anorexia (24,32,57,60,64). Herein, we examined specifically the efficacy of rikkunshito in ameliorating anorexia symptoms in our novel cancer cachexia rat models.…”
mentioning
confidence: 99%
“…Rikkunshito, which was obtained from Tsumura (Tokyo, Japan), has 8 main constituents: Glycyrrhizae radix (4.7 %), Zingiberis rhizoma (2.3 %), Atractylodis lanceae rhizoma (18.6 %), Zizyphi fructus (9.3 %), Aurantii nobilis pericarpium (9.3 %), Ginseng radix (18.6 %), Pinelliae tuber (18.6 %), and Hoelen (18.6 %). More detailed descriptions of all the substances that are known to be included in rikkunshito are found in a previous report [26]. Patients who had undergone gastrectomy invariably received 2.5 g of rikkunshito before each meal (7.5 g/day) for 4 weeks.…”
Section: Rikkunshito Administrationmentioning
confidence: 99%